2021
DOI: 10.1002/mp.15242
|View full text |Cite
|
Sign up to set email alerts
|

Experimental acoustic characterization of an endoskeletal antibubble contrast agent: First results

Abstract: An antibubble is an encapsulated gas bubble with an incompressible inclusion inside the gas phase. Current-generation ultrasound contrast agents are bubble-based: they contain encapsulated gas bubbles with no inclusions. The objective of this work is to determine the linear and nonlinear responses of an antibubble contrast agent in comparison to two bubble-based ultrasound contrast agents, that is, reference bubbles and SonoVue TM . Methods: Side scatter and attenuation of the three contrast agents were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(215 reference statements)
0
4
0
Order By: Relevance
“…An alternative carrier to conventional microbubbles has recently emerged in the form of Pickering-stabilized antibubbles. , Antibubbles consist of a liquid core surrounded by a thin gas layer that separates the core from the surrounding fluid. Recently it has been shown that the liquid core causes antibubbles to oscillate asymmetrically, which gives rise to higher harmonics with nonlinear scattering strengths comparable to or higher than those for conventional microbubble contrast agents. , The nonlinear radius oscillations may also provide a mechanism to more easily burst the antibubble and deliver a payload from the core, avoiding the surface modifications required by microbubble techniques. Further functionalities can be added to antibubbles by appropriate payload selection.…”
Section: Acoustic Responses For Smart Materialsmentioning
confidence: 99%
“…An alternative carrier to conventional microbubbles has recently emerged in the form of Pickering-stabilized antibubbles. , Antibubbles consist of a liquid core surrounded by a thin gas layer that separates the core from the surrounding fluid. Recently it has been shown that the liquid core causes antibubbles to oscillate asymmetrically, which gives rise to higher harmonics with nonlinear scattering strengths comparable to or higher than those for conventional microbubble contrast agents. , The nonlinear radius oscillations may also provide a mechanism to more easily burst the antibubble and deliver a payload from the core, avoiding the surface modifications required by microbubble techniques. Further functionalities can be added to antibubbles by appropriate payload selection.…”
Section: Acoustic Responses For Smart Materialsmentioning
confidence: 99%
“…Microbubble populations stabilised with these hydrophobised silica particles had been studied as controls at low acoustic amplitudes. 33) These populations had been measured to have a mean radius of 3 µm. Panfilova et al estimated the bulk resonance frequency near 1 MHz.…”
Section: /12mentioning
confidence: 99%
“…Panfilova et al estimated the bulk resonance frequency near 1 MHz. 33) A quantity of 5 mg of freeze-dried material was deposited into a FALCON ® 15 mL…”
Section: /12mentioning
confidence: 99%
See 1 more Smart Citation